Absence of infection by Trichinella spp. (Nematoda: Trichinellidae) in free-living wild carnivores in Brazil - Andrade, Lívia de Oliveira; Perin, Patricia Parreira; Arias-Pacheco, Carmen Andrea; Amorim, Camilla de Souza; Lefort, Fernanda; Pereira, Fernanda Mara Aragão Macedo; Soares-Neto, Lauro Leite; Bordignon Fernandes, Antonio de Pádua; Oliveira, Wilson Junior; Ichikawa, Ricardo Shoiti; da Costa, André Luiz Mota; Ruffino, Paulo Henrique Peira; et al. (Frontiers in Tropical Diseases, 2025)
BackgroundNematodes of the genus Trichinella are foodborne zoonotic pathogens that are widespread globally. These parasites have two epidemiological cycles, domestic and sylvatic, with the latter having wild carnivores as the main reservoirs of the parasite. Trichinella spp. have been increasingly detected in wild carnivores in Argentina and Chile. Although the disease is absent in domestic animals in Brazil, there is serological evidence that the agent is circulating in wild boars in some areas. This study aimed to diagnose Trichinella spp. infection through artificial tissue digestion and histopathology of selected tissues of wild carnivores from São Paulo state, southeastern Brazil.MethodsTissue samples (forearm muscles, diaphragm, and tongue) from 53 wild carnivores (21 Canidae, 25 Felidae, 04 Mustelidae, 03 Procyonidae) were used, along with a retrospective study of the slide bank, considering samples from the period 2010 to 2021, totaling 89 free-living carnivores (42 Canidae, 42 Felidae, 03 Mustelidae, 02 Procyonidae).ResultsEither artificial digestion or histopathological analyses did not reveal any larvae suggestive of Trichinella spp., indicating that the nematode was not circulating within the target population.ConclusionTo date, there is no direct evidence of nematode circulation in wild carnivores in the study area.